A possible role of essential oil terpenes in the management of childhood urolithiasis. Issue 2 (March 2005) - Al-Mosawi, Aamir Jalal
Background: Most treatments for childhood urolithiasis are preventive, and conservative management such as chemical dissolution has its limitations. As a result, open surgery is still required in childhood lithiasis. With lithotripsy, repeated sessions are often required, a uretral stent may be required and the shock wave may damage the renal parenchyma, particularly when nephrocalcinosis is present. Some authors have reported the disappearance of radiological-proven calculi in adult patients in association with the use of nontoxic terpenes, the essential oils contained in the roots, seeds and leaves of various plants.Patients & methods: From January 2001 to November 2004, 6 patients (5 males and 1 female) with ultrasonographically proven renal or uretral stones were enrolled in a clinical study investigating the possibility of using terpene oily capsules in the management of childhood urolithiasis. A total of 4 children had hypercalciuria and 2 had hyperoxaluria and distal renal tubular acidosis. Their ages ranged from 10 months to 5 years. They received traditional treatments for the underlying metabolic abnormalities, such as hypocalciuric diuretics for hypercalciuria.Aim: To provide children with sonographically proven urolithiasis, a stone-free state by the addition of essential oil capsules of the terpenic type to traditional preventive therapies. They received these therapies for a period ranging from 10 days to 12 weeks. Results: All patients achieved a stone-free state without the occurrence of any adverse effects. Conclusion: Terpenes may be of benefit in the management of childhood urolithiasis. A study enrolling a larger number of patients investigating the efficacy of these terpenes in the management of childhood urolithiasis is recommended as the small number of patients in this study preclude a definite conclusion.